The glottis is not round: Teardrop‐shaped glottic dilation for early posterior glottic stenosis. (27th December 2018) - Rosen, Clark A.; Wang, Hailun; Cates, Daniel J.; Smith, Libby J.
Abstract : Objectives: Posterior glottic stenosis (PGS) results in severe derangement of laryngeal configuration and function with significant morbidity as a sequalae. Presently, there is no treatment for patients with "early" PGS. Dilation is often used for stenotic disease, but present dilation methods are limited to a round shape and the glottis is a sector (teardrop‐shaped). Round dilation of the larynx results in compression of the membranous vocal folds (with potential for injury) and minimal expansion of the posterior larynx. We present a novel laryngeal dilation method that matches the unique anatomic shape of the glottis: teardrop‐shaped glottis dilation (TSGD). Methods: We present a clinical series of early PGS patients treated with a TSGD. Five patients with dyspnea and significantly reduced vocal fold mobility due to early PGS were treated with TSGD, which involves placement of a triangular static stent in the anterior glottis, with simultaneous use of a round balloon dilator in the posterior glottis. Results: All patients reported improved ease of breathing and decrease in Dyspnea Index score and were decannualated following treatment. Video perceptual analysis of pre‐/postlaryngoscopy examinations was performed with five blinded reviewers, and all patients were scored to have improved posterior glottic airway space following treatment with a mean improvement of 2.4 on a 11‐point scale. Conclusion: These clinical results demonstrate that there is enormous potential for the identification and treatment of patients with early PGS and use of a laryngeal dilation technique that matches the anatomic configuration of the glottis. Level of Evidence: 4 Laryngoscope, 129:1428–1432, 2019